2009
DOI: 10.1063/1.3125315
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective electroplated nickel mask for lithium niobate dry etching

Abstract: International audienceA sulfur hexafluoride based reactive ion etching process allowing to etch several micron deep holes with diameters of the order of a few microns in lithium niobate is reported. Etching of deep structures with aspect ratios up to 1.5 was made possible through the use of an electroplated nickel mask exhibiting a selectivity as high as 20 with respect to lithium niobate. Several crystallographic orientations were investigated, although particular interest was paid to Y-axis oriented substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…The wafer is then flip-bonded to the LN carrier wafer using glue, and ground down to 1um thickness. Traditionally, reactive ion etching (RIE) is used for anisotropic etching of LN [8], [15], where metal or oxide hard mask and very high RF power are used. However, it is very hard to achieve >80 degrees side-wall verticality due to the re-deposition of lithium compound [16].…”
Section: Fabricationmentioning
confidence: 99%
“…The wafer is then flip-bonded to the LN carrier wafer using glue, and ground down to 1um thickness. Traditionally, reactive ion etching (RIE) is used for anisotropic etching of LN [8], [15], where metal or oxide hard mask and very high RF power are used. However, it is very hard to achieve >80 degrees side-wall verticality due to the re-deposition of lithium compound [16].…”
Section: Fabricationmentioning
confidence: 99%
“…The aspect ratio of the large kerf (≥ 10 μm) etching is up to 1.3, while for the smaller kerf it decreases gradually. As the aspect ratio reduces to about 1 [19], it has been suggested that the etching rate begins to be limited by transport of etch gases into the kerf and etch products out of the kerf. For closely spaced structures, this would result in profile angles less than 60°, which is unacceptable for fabricating high-frequency arrays.…”
Section: B Icp Riementioning
confidence: 99%
“…An ICP reactive ion etching system (from Surface Technology System company) with multiplex AOE reactor was used, which employed CF 4 based chemistry, for the etching process. At 750 W of ICP power, a DC bias voltage of 200 V, 20 sccm of He, and 60 sccm CF 4 , operating pressure of 0.2 Pa, the etching rate of LiNbO 3 film was 8 μm/hr, the selectivity of electroplated Ni with respect to lithium niobate is about 20 [19]. In an ideal case the kerf etching with high aspect ratio (h/d > 33 μm/7.5 μm) is required for a 100 MHz full-kerfed array.…”
Section: B Icp Riementioning
confidence: 99%
“…It is far less developed for piezoelectric materials and typically based on reactive ion etching (RIE) [e.g. [6][7][8][9]. LiNbO 3 is the more appropriate material from the electroacoustic point of view; however, it is more challenging than quartz.…”
Section: Technology Developmentmentioning
confidence: 99%